2012
DOI: 10.1515/cjal-2012-0024
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Strategies in Learning to Write a Thesis Proposal: A Study of Six M.A. Students in a TEFL Program

Abstract: This study explored how six graduate students of a TEFL (teaching English as a foreign language) program learned to write their MA thesis proposals in English in a graduate course. Multiple sources of evidence were collected, including questionnaires, interviews, classroom observations, and presentation profiles. Data analyses showed that the students encountered difficulties in selecting a research topic, designing the proposal research, grasping the genre of the thesis proposal, and doing a critical literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…To some extent, it is not anticipated that teacher-student communication was uniformly perceived by the supervisors as the other reasons. This shared perception also reinforces the views that effective collaboration and communication between supervisors and students are crucial for helping the students develop academic literacy competence (Belcher, 1994;Dong, 1998;Wang & Yang, 2012).…”
Section: From Supervisorssupporting
confidence: 68%
See 2 more Smart Citations
“…To some extent, it is not anticipated that teacher-student communication was uniformly perceived by the supervisors as the other reasons. This shared perception also reinforces the views that effective collaboration and communication between supervisors and students are crucial for helping the students develop academic literacy competence (Belcher, 1994;Dong, 1998;Wang & Yang, 2012).…”
Section: From Supervisorssupporting
confidence: 68%
“…This perception is also evident in Bitchener and Basturkmen's (2006) study, where supervisors considered that students experienced a high level of difficulty in meeting the requirements of genres while writing DRS. Additionally, there are several other studies which have indicated that Chinese undergraduates need to be explicitly exposed to the different genres of academic writing (e.g., Qian & Krugly-Smolska, 2008;Wang & Yang, 2012).…”
Section: From Supervisorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Preparing an RP is an essential part of the process of thesis preparation at the postgraduate level, which usually involves identifying a research topic, writing a proposal, conducting research, and writing up the thesis (Riazi, 2000;Wang & Yang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the preparation of an RP is difficult, for various reasons (Wang & Yang, 2012); therefore, postgraduate students should pay close attention to preparing their RP, because it is expected to:  show that [they] are engaging in genuine enquiry, finding out about something worthwhile in a particular context  link [their] proposed work with the work of others, while proving [they] are acquainted with major schools of thought relevant to the topic  establish a particular theoretical orientation  establish [their] methodological approach, and  Show [they] have thought about the ethical issues (Monash University, 2014, p. 2).…”
Section: Introductionmentioning
confidence: 99%